Power Amplifiers for the S-, C-, X- and Ku-bands An EDA Perspective - Božanić, Mladen; Sinha, Saurabh (Signals and Communication Technology,, 2016)
This book provides a detailed review of power amplifiers, including classes and topologies rarely covered in books, and supplies sufficient information to allow the reader to design an entire amplifier system, and not just the power amplification stage. A central aim is to furnish readers with ideas on how to simplify the design process for a preferred power amplifier stage by introducing software-based routines in a programming language of their choice. The book is in two parts, the first focusing on power amplifier theory and the second on EDA concepts. Readers will gain enough knowledge of RF and microwave transmission theory, principles of active and passive device design and manufacturing, and power amplifier design concepts to allow them to quickly create their own programs, which will help to accelerate the transceiver design process. All circuit designers facing the challenge of designing an RF or microwave power amplifier for frequencies from 2 to 18 GHz will find this book tobe a valuable asset.